Women's Reproductive Freedom in Indonesia: Perspectives of Human Rights and Social Norms - Siti Maratus Solihah; Aghnia Wafda Islaha; Fatma Zuliantika; Aini Rahmania (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
Reproductive rights can be defined as personal freedoms recognized under human rights, particularly for women. The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) emphasizes that women have the right to make decisions regarding reproduction, including the right to choose whether or not to have children, as well as the right to access reproductive health services. Issues related to women's reproductive rights are part of the broader concept of freedom, which encompasses the right to self-determination over one's body and life. In Indonesian society, perspectives on reproduction often reflect cultural norms and religious beliefs that view childbearing as a woman's duty after marriage. From these viewpoints, reproduction is considered an obligation for a wife to continue the lineage. A woman is often not regarded as a "complete" wife unless she can bear children. Frequently, neighbors, exte.nded family members, and even husbands pressure women to conceive and give birth, perceiving it as an intrinsic duty of a wife after marriage. This perspective also leads women to feel that having children is an obligation they must fulfill. If they do not have children-either yet or at all-they often see themselves as having failed to meet their perceived responsibilities.